Mobility as a Service Inclusion Index (MaaSINI): Evaluation of inclusivity in MaaS systems and policy recommendations. (October 2022) - Dadashzadeh, Nima; Woods, Lee; Ouelhadj, Djamila; Thomopoulos, Nikolas; Kamargianni, Maria; Antoniou, Constantinos
Abstract: According to UN statistics, the population of people in vulnerable social groups, namely elderly people, people with disabilities, and low-income populations, has increased over the recent decades. It is projected that this trend will continue in the future. Thus, their mobility and access to transport services are important areas to study. Mobility as a Service (MaaS) is a digital platform (smartphone application) that aims to encourage more sustainable travel. MaaS is promoted as being accessible to all user groups. However, there are limited studies linking MaaS with vulnerable social groups and their particular needs. This paper comprehensively reviews studies on the emergence of such platforms since 2014 until today to identify the research gaps with respect to vulnerable social groups. A framework and MaaS Inclusion Index (MaaSINI) are then proposed to evaluate the inclusion in MaaS services, focusing on vulnerable social groups' needs at a service level instead of a city/area level. The framework and policy recommendations proposed in this study will make a significant contribution in guiding stakeholders and policymakers in implementing accessible-for-all-users MaaS services targeting sustainable and inclusive transport. Highlights: This work includes a comprehensive review of existing MaaS studies with respect to Vulnerable Social Groups' (VSGs) needs. Supply and demand side of MaaS systems are discussed considering VSGs' needs. A novel MaaS Inclusion Index (MaaSINI) is proposed to evaluate the inclusiveness of MaaS systems. A real-World MaaS app and some other scenarios are evaluated using the proposed MaaSINI framework. Directions for future research and policy implications are proposed.